(untitled) (Research, Society and Development, 2022)
Nursing workers face numerous psychological suffering, being exposed to a variety of elements that generate wear. To stay healthy, professionals develop strategies and protective factors such as resilience. This study aimed to assess resilience among nursing professionals in emergency sectors in the city of São José do Rio Preto (SP) and compare it with the number of employment relationships. This is a quantitative, descriptive, correlational and cross-sectional study, which used the data collection instruments Questionnaire of Sociodemographic and Professional Variables and the Wagnild & Young Resilience Scale. A total of 144 professionals, including assistants, technicians and nurses participated in the study. In the results, of the 144 participants, 18 (12.5%) work more than 44 hours per week, 29 (20.1%) work more than one shift and 33 (22.9%) accumulate, with 30 (20, 8%) with 2 and 3 (2.1%) with 3 bonds; of those who accumulate 21 (14.6%) put the financial need as motivation and 12 (8%) the search for better remuneration. High resilience rates (mean 136.4) among participants, with no significant difference with the number of hours worked (p = 0.438), work shift (p = 0.959) or number of employment relationships (p = 0.390). It can be concluded that the nursing professionals in this study exhibit high levels of resilience, even with the exhausting routine, demonstrating love, pride and professional commitment, regardless of working hours, work shifts and number of employment relationships, among others.